Оптико-волоконное скопирование в литье и металлургии - Марков А. П. Алексей Петрович; Марукович Е. И. Евгений Игнатьевич; Потапкин В. В. Вадим Вадимович; Старовойтов А. Г. Анатолий Григорьевич (Минск, Беларуская навука, 2010)
На обл. авт. не указан